Strain effect on the electronic and optical characteristics of FAGeX3 (X=Cl, Br, and I) perovskite materials: DFT analysis - Haque, Md. Mahfuzul; Amanullah, Md; Mia, Md. Roman; Islam, Md. Rasidul (Heliyon, 2024)
This study investigates the electronic and optical properties of a perovskite material known as Formamidinium Germanium Halide (FAGeX3), where X represents the elements Chlorine (Cl), Bromine (Br), and Iodine (I). We explore the bandgap, density of state (DOS), and partial density of state (PDOS) to understand their electronic properties. We use two methods, PBE and HSE-06, to determine the bandgap. Further, we investigate the optical properties by investigating the real and imaginary functions of the dielectric constant, refractive index, electron energy loss function, and absorption coefficient. Our research extends to the impact of biaxial strain, both tensile and compressive, in the −6% to +6 % range. Without strain, the materials exhibit direct bandgaps at the R point, with FAGeCl3 showing the highest bandgap (2.1359 eV), followed by FAGeBr3 (1.7325 eV), and FAGeI3 with the lowest (1.2581 eV). Our results reveal that applying tensile strain increases the bandgap and induces a blueshift, shifting the optical responses to shorter wavelengths, while compressive strain reduces the bandgap and causes a redshift, enhancing longer wavelength responses. Our findings demonstrate that FAGeX3 perovskites exhibit highly tunable electronic and optical properties under strain, making them exceptional candidates for advanced optoelectronic applications.